Interval training has more negative effects on sleep in adolescent speed skaters: a randomized cross controlled trial - Zhenxing, K.; Wei, X.; Shen, M.; Cheng, Y.; Feng, J. (Frontiers in Sports and Active Living, 2024)
Objective: Sleep is an essential component of athletic performance and recovery. This study aimed to investigate the effects of different types of high-intensity exercise on sleep parameters in adolescent speed skaters.